Minutes of meeting of Basque Administrative Sub-Committee
1939-06-13 038-0094-001 MINUTES OF MEETING OF BASQUE ADMINISTRATIVE SUB-COMMITTEE HELD ON TUESDAY, JUNE 13TH, 1939, AT 30 ECCLESTON STREET, S.W.1. PRESENT: Mrs. Attenborough (in the Chair) Dr. Ellis, Mrs. Gee Mr. Fuller Bryant Mr. Thackrah Miss Vulliamy Miss Hawes Mr. Rickard Mr. Harman Mr. Kavanagh Dr. Betty Morgan Dr. Camps Miss Smith Miss Garrett Miss Stewart Miss Holland Miss Picken 1. APOLOGIES FOR ABSENCE - read from Miss Pye Dr. Morgan stated that some members were attending the British Refugee Committee, now fixed for Tuesday afternoons, and asked those present if some other time could be fixed for the Basque Administrative Sub-Committee. Mondays at 5 p.m. was agreed. 2. MINUTES OF THE LAST MEETING. The Minutes of the last meeting having been circulated were taken as read and signed. 3. MATTERS ARISING ON THE MINUTES. (a) Cambridge - Dr.Camps' Report. Dr. Camps reported that she had visited Cambridge as arranged. She had discussed the position of staff at this Centre, where the vacancies had been filled. There were now two Wardens - Mrs. Ecroyd and Sra. Martinez, for whom Cambridge had been waiting some months, and who had just arrived from France. Dr. Camps thought the two Wardens would work amicably together, one as Assistant. Cambridge was also anxious to know whether or not the 7 children - daughters of Militia men with mothers in Spain should be repatriated. After discussion it was thought that the whole question of repatriation - in view of reports on conditions in Spain - should be brought up at the main Committee. At this point Dr. Morgan reported that a cable had been received from San Sebastian from Dr. Byloff stating that her investigations in the Basque country were completed, and asking where she should send the information obtained. Mr. Kavanagh who was going to Hendaye offered to see Dr. Byloff at the frontier and obtain her impressions. Agreed to send Dr. Byloff a cable asking her to meet Mr. Kavanagh at Hendaye. Recommendations from Closing of Homes Sub-Committee. (b) Bray Court. At the last Committee Meeting the closing of certain homes (including Bray Court) was referred to the Closing of Homes Sub-Committee. Mr. Thackrah and Mr. Fuller Bryant stated that the sub-Committee had considered the position at 292/946/38/94(I)